The Influence of IT, Regulation, and SDG on the Quality of LSK Operations through BPI - Desita Budiharsanti; Tukhas Shilul Imaroh (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the influence of Information Technology Implementation, Regulatory Compliance, and Commitment to Sustainable Development Goals (SDGs) on Operational Quality, with a particular focus on the mediating role of Business Process Improvement (BPI). The research is motivated by the operational inefficiencies observed in certification bodies amid increasing demands for digitalization, regulatory adherence, and sustainability integration. A quantitative approach was adopted, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. Data were collected through a structured survey distributed to internal stakeholders at PT XYZ, a certification organization, and analyzed using SmartPLS 4.0. The findings reveal that all three independent variables—information technology implementation, regulatory compliance, and SDG commitment—positively and significantly influence operational quality. Moreover, Business Process Improvement is found to partially mediate the relationship between each independent variable and operational quality. These results reinforce the theoretical perspective that technology, compliance, and sustainability initiatives yield optimal impact when translated into systematic process improvement efforts. The study highlights the strategic role of BPI as a mechanism that bridges organizational strategy with operational execution. It is recommended that organizations not only invest in digital systems and regulatory alignment but also redesign internal processes to holistically meet performance, efficiency, and sustainability goals.